psychology-cognition 2016
DOI: 10.35841/psychology-cognition.1.1.57-63
|View full text |Cite
|
Sign up to set email alerts
|

Treatment by repeating phrases of positive thoughts (TRPPT): A new effective treatment tool against psychological troubles (PSYT) (Depression, anxiety, stress, low self-esteem and dissatisfaction in life) in multiple sclerosis patients and students, a controlled and randomized pilot study.

Abstract: Introduction: Psychological troubles (PSYT) are common co-morbidities symptoms in multiple sclerosis (MS). Negative verbal thinking style plays a causal role in maintaining intrusions, perhaps serving to trigger subsequent depressive and anxious symptoms and psychological distress. Positive verbal thinking style plays protective role against these symptoms. Objective: The objective of this study was the first to evaluate the short-term effects of the TRPPT method (Treatment by Repeating Phrases of Positive Tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Attempts to change such were noted among many of the participants despite there being little research to support whether thinking patterns are recognized as contributing to the experience of stress among women or whether chronic stress contributes to behavior becoming habitual. However, one mixed gender study which allocated student volunteers ( n = 44 [11 men and 33 women]) to either an experimental group ( n = 21) that repeated positive thoughts in the presence of feelings of anxiety, depression or stress, or a control group ( n = 23) which did not, revealed that positive thinkers experienced a reduction in such mental states including a reduction in stress (Alsaleh, Lebreuilly, Tostain, & Lebreuilly, 2018). Furthermore, a study that investigated women ( n = 98) with fibromyalgia found that high levels of rumination, defined as a “thinking style that generates re‐current repetitive, intrusive and uncontrollable thoughts” were correlated with stress as measured using the perceived stress scale (Malin & Littlejohn, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to change such were noted among many of the participants despite there being little research to support whether thinking patterns are recognized as contributing to the experience of stress among women or whether chronic stress contributes to behavior becoming habitual. However, one mixed gender study which allocated student volunteers ( n = 44 [11 men and 33 women]) to either an experimental group ( n = 21) that repeated positive thoughts in the presence of feelings of anxiety, depression or stress, or a control group ( n = 23) which did not, revealed that positive thinkers experienced a reduction in such mental states including a reduction in stress (Alsaleh, Lebreuilly, Tostain, & Lebreuilly, 2018). Furthermore, a study that investigated women ( n = 98) with fibromyalgia found that high levels of rumination, defined as a “thinking style that generates re‐current repetitive, intrusive and uncontrollable thoughts” were correlated with stress as measured using the perceived stress scale (Malin & Littlejohn, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…to either an experimental group (n = 21) that repeated positive thoughts in the presence of feelings of anxiety, depression or stress, or a control group (n = 23) which did not, revealed that positive thinkers experienced a reduction in such mental states including a reduction in stress (Alsaleh, Lebreuilly, Tostain, & Lebreuilly, 2018).…”
Section: Thinking Patterns and Stressmentioning
confidence: 98%
“…It's observed that MS patients think negatively according to mean of T-score. In War, the mean scores of negative and positive automatic thoughts in students and MS patients were vary (positive automatic thoughts increase and negative automatic thoughts decrease) when the positive and cognitive psychotherapy has been applied [1,8,9,11]. So, provide of the psychological-social support and treatment for victims of war and refugees are very important in war.…”
Section: Discussionmentioning
confidence: 99%
“…In study in 2011 on adolescents [7], prevalence rates were 4.59% for state anxiety, 4.84% for trait anxiety, and 7.90% for depression. In War in Syria, the Syrian adults are suffering from depressive symptoms; and the mental and psychiatric disorders are one of the most common disorders in war conditions [1,4,8,10,11,52]. In War, in 2015-2016, the prevalence of depression evaluated by BDI-FS-Ar was 79.00% in students at Damascus University, and 63.00% in multiple sclerosis (MS) patients in Syria [4,10].…”
mentioning
confidence: 99%
“…In War in Syria, the Syrian adults are suffering from depressive symptoms; and the mental and psychiatric disorders are one of the most common disorders in war conditions Alsaleh M [1,2], Kubitary [3,10]. Before War, Radwan [4] found that severe depression using BDI-II affects 5.4% of Damascus University students Radwan [4], Kubitary [10].…”
Section: Introductionmentioning
confidence: 99%